Permainan Tradisional untuk Mengatasi Adiktif Gawai pada Anak di Desa Alastuwo - Joni Rusdiana; Putri, Haura Sabita (Transformatif : Jurnal Pengabdian Masyarakat, 2022)
The recommendation of the PPPA Ministry is that children should ideally be allowed to use gadgets after they are at least 13 years old. However, the fact is that in Alastuwo Village, Kebakkramat, Karanganyar, many children under the age of 13 are addicted to gadgets. For this reason, the UIN Raden Mas Said Surakarta service team intends to provide a solution to this problem through a traditional game outreach program. The method used is Participatory Action Research (PAR) by actively participating in activities with the subject of Alastuwo Village children who are studying from kindergarten to elementary school. There are three types of games that we socialize. They are jumping rope, marbles, and gobak sodor. This program shows positive results, that are evidenced by the reduced frequency and intensity of using gadgets in children. In addition, this game is also continuously repeated by children in the following days along with peers. We hope that this program can be recommended and carried out in other areas experiencing similar problems, both with the same game and other types of traditional games.